2023
DOI: 10.3390/d15040579
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diversity and Dynamics during Long-Term Immersion of Conventional and Biodegradable Plastics in the Marine Environment

Abstract: Plastics are associated with a worldwide pollution crisis, with strong negative impacts on both terrestrial and aquatic ecosystems. In marine environments, various organisms are colonizing plastic debris, but few studies have focused on fungal communities despite their non-trivial ecological roles in the marine environment. In this study, different types of plastics (biodegradable and conventional) immersed in marine natural environments and under laboratory controlled settings were collected after long-term c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 89 publications
2
8
2
Order By: Relevance
“…These included the genera Cystobasidium, Vishniacozyma, Bjerkandera, and Stereum. Many studies report fungi from plastic materials, but contrary to our results, higher numbers of Ascomycota are usually reported [57].…”
Section: The Choice Of Building Materials Makes Selective Pressure On...contrasting
confidence: 99%
“…These included the genera Cystobasidium, Vishniacozyma, Bjerkandera, and Stereum. Many studies report fungi from plastic materials, but contrary to our results, higher numbers of Ascomycota are usually reported [57].…”
Section: The Choice Of Building Materials Makes Selective Pressure On...contrasting
confidence: 99%
“…However, these results diverge from those of Sérvulo et al (2023), who reported stable communities over a 1-year immersion period. In terms of taxonomic diversity, Ascomycota dominate plastic-associated fungal communities, where other fungal phyla are also present (De Tender et al, 2017;Kettner et al, 2017;Lacerda et al, 2020Lacerda et al, , 2022Philippe et al, 2023;Sérvulo et al, 2023;Zeghal et al, 2021), which aligns with the general patterns in pelagic marine fungal diversity (Jones et al, 2019). Moreover, plastic-associated Chytridiomycota exhibit higher abundance during the autumn and winter seasons (Sérvulo et al, 2023) or at higher latitudes (Kettner et al, 2017;Kirstein et al, 2018).…”
Section: Plastic-associated Fungisupporting
confidence: 69%
“…Only one study detected differences in community composition, of fungal communities on polystyrene and PET, which contrasted with those on polyurethane (S. Yang et al., 2022). A recent study comparing fungal colonization on conventional versus biodegradable plastics underscores the significant impact of immersion duration on fungal colonization (Philippe et al., 2023). This is supported by temporal variability observed in fungal communities (De Tender et al., 2017).…”
Section: Biogeochemical Impacts Of Planktonic Marine Fungimentioning
confidence: 99%
“…In addition, their association with eukaryotic organisms, such as (micro)algae and invertebrates, which are indeed common plastisphere inhabitants [ 17 , 18 ], would explain their dominance. Fungi are also common members of the marine plastisphere, even though they have not been well-evaluated, despite their non-trivial ecological roles in marine environments [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%